# Calculus

posted by .

Derive:
F(x)= sqrt(3, 1 + tan(x))

• calculus - eh? -

The verb is differentiate, not derive.

I have no idea what the formula is. sqrt just has one argument. what does

sqrt(3, 1 + tan(x))

mean?

## Similar Questions

1. ### calculus

How do I derive the integration reduction formula for tangent?
2. ### calculus

Calculate definite integral of dx/(x^4 * sqrt(x^2 + 3)) Over (1,3) I start with the substitution x = sqrt(3)*tan t so: sqrt(x^2 + 3) = sqrt(3) * sec t dx = sqrt(3) * sec^2 t dt x^4 = 9 * tan^4 t The integral simplifies to: = dt/(tan^3 …
3. ### calculus

Integrate: dx/sqrt(x^2-9) Answer: ln(x + sqrt(x^2 - 9)) + C I'm getting the wrong answer. Where am I going wrong: Substitute: x = 3 * sec t sqrt(x^2 - 9) = sqrt(3) * tan t dx = sqrt(3) * sec t * tan t Integral simplifies to: sec t …
4. ### Calculus

Calc length of arc of y=ln(x) from x=1 to x=2 ---- So far: Definite Integral over x=(1,2) of sqrt(1 + 1/x) dx 1/x = tan^2 t x = 1/tan^2 t sqrt(1+1/x) = sqrt(1+tan^2 t) = sec t dx = -2 * tan^-3 t * sec^2 t dt Integrate over x=(1,2): …
5. ### Pre Cal.

Evaluate tan(cos^(-1)(ã3/2 )+tan^(-1)(ã3/3))?
6. ### Math

1.Write the equation 5x+y-2=0 in normal form. 5x+y-2=0 5x+y=2 (add two to both sides) Standard form (Ax+By=C)---> 5x+y=2 Y-intercept (when x equals 0) 5x+y-2=0 5x+y=2 5(0) +y=2 y=2 X-intercept (when y equals 0) 5x+y-2=0 5x+y=2 5x+0=2 …
7. ### calculus

find functions f(x) and g(x) so that f(g(x))= sqrt(tan(3x^2 - 7)) Would this work?
8. ### Math

tan(-120)= sqrt 3 OR - sqrt 3 (Helper stated that it was sqrt 3) But, I'm just confused over this part: for even vs. odd functions it saids that tan(-angle) = - tan(angle) so the even vs. odd doesn't matter since tan is positive in …
9. ### calculus

The question is: tan(arcsinx)= I know that inverse of sin is 1/sqrt(1-x^2) however this question still confuses me. The outcome is x/sqrt(1-x^2), how did the tan create the additional x ?
10. ### calculus

The question is: tan(arcsinx)= I know that inverse of sin is 1/sqrt(1-x^2) however this question still confuses me. The outcome is x/sqrt(1-x^2), how did the tan create the additional x ?

More Similar Questions